Proposta de um modelo matemático para o problema dial-a-ride aplicado ao transporte de cadeirantes - Rodrigues, Patrícia Perretto (2011)
Problems that deal with wheelchair users’ public transportation are often solved by Dial a Ride Problem (DARP) with time window (Time Window – TW). The goal of this type of problem is the minimization of the operation cost, in other words, the ride time respecting constraints like time windows for pickup and delivery of each user, the number of vehicles available and each vehicle capacity. This thesis proposes an exact Mixed Integer Linear Program model to solve the DARPTW. In order to apply the model in a real application, the model was tested with data provided by the Vitória City Hall Infrastructure and Transportation Secretary. The model was implemented using CPLEX software and the results showed that instances up to 20 wheelchair users’ can be solved optimally. Moreover, it was done an analysis for fleet used.